Wine and the Marketing Mix: An Analysis of New Zealand Wine Brands in the UK Off Trade - Wellings, Antony David (2005)
The global wine industry is in a period of immense change. Traditionally, production driven, the industry now finds itself in an increasingly competitive global market place, where branding and a marketing driven approach are considered the key to future success. In the UK wine market (especially the off trade), where competition is particularly fierce, it is New Zealand wine brands which appear to have marketed themselves well in the past. They may only account for a relatively small percentage of overall sales, but they command an enviable price premium and have enjoyed considerable success over the past decade. It has been suggested that all this may be about to change, with increased production putting downward pressure on pricing. Effective marketing is therefore seen as more critical than ever.